Structural and optical studies of (Ag₃AsS₃)₀.₆(As₂S₃)₀.₄ thin films deposited at different technological conditions - Studenyak, I.P.; Neimet, Yu.Yu.; Rati, Y.Y.; Buchuk, M.Yu.; Kökényesi, S.; Daróci, L.; Bohdan, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
(Ag₃AsS₃)₀.₆(As₂S₃)₀.₄ thin films were deposited upon a quartz substrate by rapid thermal evaporation at temperatures 1050, 1200, and 1350 °C. Structural studies of the as-deposited thin films were carried out by scanning electron microscopy and atomic force microscopy. It is shown that the surfaces of all the films were covered with Ag-rich crystalline micrometer sized cones. The optical transmission spectra for as-deposited thin films were studied at room temperature. The absorption spectra in the region of its exponential behaviour were analyzed, the dispersion dependences of refractive index as well as their variation depending on evaporation temperature were investigated.